Rice black-streaked dwarf virus P10 promotes phosphorylation of GAPDH (glyceraldehyde-3-phosphate dehydrogenase) to induce autophagy in Laodelphax striatellus. Issue 4 (3rd April 2022) - Wang, Qi; Lu, Lina; Zeng, Ming; Wang, Dan; Zhang, Tian-ze; Xie, Yi; Gao, Shi-bo; Fu, Shuai; Zhou, Xue-ping; Wu, Jian-xiang
ABSTRACT: Macroautophagy/autophagy is an important innate and adaptive immune response that can clear microbial pathogens through guiding their degradation. Virus infection in animals and plants is also known to induce autophagy. However, how virus infection induces autophagy is largely unknown. Here, we provide evidence that the early phase of rice black-streaked dwarf virus (RBSDV) infection in Laodelphax striatellus can also induce autophagy, leading to suppression of RBSDV invasion and accumulation. We have determined that the main capsid protein of RBSDV (P10) is the inducer of autophagy. RBSDV P10 can specifically interact with GAPDH (glyceraldehyde-3-phosphate dehydrogenase), both in vitro and in vivo . Silencing of GAPDH in L. striatellus could significantly reduce the activity of autophagy induced by RBSDV infection. Furthermore, our results also showed that both RBSDV infection and RBSDV P10 alone can promote phosphorylation of AMP-activated protein kinase (AMPK), resulting in GAPDH phosphorylation and relocation of GAPDH from the cytoplasm into the nucleus in midgut cells of L. striatellus or Sf9 insect cells. Once inside the nucleus, phosphorylated GAPDH can activate autophagy to suppress virus infection. Together, these data illuminate the mechanism by which RBSDV induces autophagy in L. striatellus, and indicate that the autophagy pathway in an insect vector participates in the anti-RBSDV innate immune response. Abbreviations 3-MA: 3-methyladenine; AMPK: AMP-activated protein kinase; ATG: autophagy-related; co-IP: co-immunoprecipitation; DAPI: 4ʹ, 6-diamidino-2-phenylindole; dpf: days post-feeding; dsRNA: double-stranded RNA; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GST: glutathione-S-transferase; RBSDV: Rice black-streaked dwarf virus; TEM: transmission electron microscope.